Water Demand Analysis and Irrigation Requirement for Major Crops at Holetta Catchment, Awash Subbasin, Ethiopia - Tibebe, M.; Zemadim, Birhanu (2015)
The water demand and irrigation requirement of Holetta Catchment is not fully studied. In addition to this, due to scarcity of the available surface water and increase in water demand for irrigation, the major users of the river are facing a challenge to allocate the available water. Therefore, the aim of this research was to investigate the water demand of the major users of Holetta River and to study the irrigation requirement for major crops at Holetta catchment using questionnaire survey, statistical methods, and CropWat model. Structured questionnaire was used to identify information such as the number of Holetta River users, major crops grown by irrigation and the total area coverage. The major users are Holetta Agricultural Research Center (HARC), Tesdey Farm and Village Farmers. CropWat model was used to calculate the irrigation water requirement for major crops. Based on the result of CropWat model and survey analysis, the total irrigation requirement of all three users of Holetta River was 0.305, 0.575, 0.995, 0.865, and 0.332 MCM for January, February, March, April, and May respectively. The analysis also indicated the total water demand of all three major users of Holetta River during the irrigation season from January to May. The total water demand was 0.313, 0.583, 1.004, 0.873 and 0.341 million cubic meters (MCM) for January, February, March, April, and May respectively. The available river flow from January to May was 0.749, 0.419, 0.829, 0.623 and 0.471 MCM respectively. From the five months, the demand and the supply showed a gap during February, March and April. The total shortage of supply during these months was 0.59MCM. During these months, there was also conflict between users at diversion and water allocation. Therefore, in order to solve water shortage, alternative source of water supply like ground water and water harvesting technologies should be studied and integrated water management system should be implemented. In addition to this, to improve the efficiency of irrigation water, different irrigation methods like drip irrigation should be improved in the area.